Valor y Juventud - Valenzuela, Fernando (Revista Chilena de Humanidades, 2016)
Prof. Valenzuela singles out peculiar traits ol the adolescent's lile, whilestating the interest of philosophy in the ethical component in the behaviourof the young. This study also emphasizes motivations, attitudes, and valuesystems which express the desire of young people to conquer a position thougha new order, one in which their own sense of things is projected. Prof. Valenzuelagives great importance to the participation of youth in social life, froma philosophica] perspective which acknowledges its own limitations.